Dynamics of the particular and the common: Monuments and patriotic tourism in socialist Yugoslavia – a case study of Kosovo - Agata Rogoś (Slavia Meridionalis, 2019)
Dynamics of the particular and the common: Monuments and patriotic tourism in socialist Yugoslavia – a case study of Kosovo